Marketing for dummies - McMurtry, Jeanette Maw (--For dummies., 2022)
In a post-pandemic, up or down economy, it's harder than ever to meet highly complex and ever-changing customer expectations. The top-selling Marketing For Dummies covers basics like sales strategy, channel selection and development, pricing, and advertising. We also teach you complex elements like personalization, customer behavior, purchasing trends, ESG ratings, and market influences. With this complete guide, you can build a business that not only competes in a challenging market, but wins. This updated edition will walk you through the latest marketing technologies and methods, including customer experience, retargeting, digital engagement across all channels and devices, organic and paid SEO, Google ads, social media campaigns and posts, influencer and content marketing, and so much more. You'll discover what works, what doesn't, and what is best for your business and budget. Learn the marketing and sales strategies that work in any economy; discover how to engage customers with trust and enthusiasm; understand post-pandemic changes in consumer attitudes; discover new tools and technologies for finding customers and inspiring loyalty; adapt your brand, pricing, and sales approach to make your business more valuable; and avoid common marketing mistakes and learn how to measure the impact of your efforts.